2001
DOI: 10.1182/blood.v97.9.2673
|View full text |Cite
|
Sign up to set email alerts
|

The interleukin-13 receptor α2 chain: an essential component for binding and internalization but not for interleukin-13–induced signal transduction through the STAT6 pathway

Abstract: IntroductionInterleukin-13 (IL-13) and IL-4 are related multifunctional cytokines with similar biological activities on human B cells and monocytes. [1][2][3][4][5][6][7] The cognate receptors for these cytokines are complex and have been shown to share 2 chains with each other. [8][9][10][11][12] The IL-4 receptor system is well characterized and has been shown to be composed of a primary IL-4 binding protein, IL-4R␣ (also known as IL-4R␤). 13 This chain forms a heterodimer with either the IL-2R␥ c chain (typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
171
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 197 publications
(176 citation statements)
references
References 38 publications
5
171
0
Order By: Relevance
“…Previous studies have demonstrated that the attachment of radiolabeled IL-13 to the functional heterodimer receptor can be competed by IL-4 as well as IL-13, [30][31][32]49 whereas its attachment to IL-13R 2 is competed by IL-13 but not IL-4. 2,9,10,15,33,36 To confirm that the cytotoxicity of IL-13 cytotoxin was specifically mediated through IL-13R 2 chain delivered by Ad-IL-13R 2 vector, A549 cells were infected with Ad-IL-13R 2 at MOI 10 followed by treatment with IL-13 cytotoxin (10 ng/ml) in the presence of a 50-fold dose of human IL-13 or IL-4. As shown in Figure 4, IL-13 and IL-4 did not affect the growth of uninfected or Ad-LacZ-infected cells, regardless of treatment with IL-13 cytotoxin.…”
Section: Il-13 But Not Il-4 Competitively Inhibits Cytotoxicity Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that the attachment of radiolabeled IL-13 to the functional heterodimer receptor can be competed by IL-4 as well as IL-13, [30][31][32]49 whereas its attachment to IL-13R 2 is competed by IL-13 but not IL-4. 2,9,10,15,33,36 To confirm that the cytotoxicity of IL-13 cytotoxin was specifically mediated through IL-13R 2 chain delivered by Ad-IL-13R 2 vector, A549 cells were infected with Ad-IL-13R 2 at MOI 10 followed by treatment with IL-13 cytotoxin (10 ng/ml) in the presence of a 50-fold dose of human IL-13 or IL-4. As shown in Figure 4, IL-13 and IL-4 did not affect the growth of uninfected or Ad-LacZ-infected cells, regardless of treatment with IL-13 cytotoxin.…”
Section: Il-13 But Not Il-4 Competitively Inhibits Cytotoxicity Ofmentioning
confidence: 99%
“…Therefore, IL-13R 1 chain requires the recruitment of IL-4R chain [30][31][32]35 to form a high-affinity heterodimer receptor complex, which mediates the IL-13 signaltransduction pathway. IL-13R 2 chain by itself can bind IL-13 with higher affinity, but it does not mediate IL-13 signaling 35,36 because it has a very short cytoplasmic domain that lacks the conserved signaling motifs. In particular, IL-13R 2 chain has a unique property of ligand internalization after binding, 36,37 which has also been identified as a soluble protein in mouse serum and urine; 38 thus, it can be a specific inhibitor of IL-13 signaling or a decoy receptor for IL-13.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, IL13Ra2 does not seem to require IL-4Ra and by itself binds IL-13 with high affinity, internalizes and also mediates signal transduction. [8][9][10][11] To determine the significance of IL-13Ra2 expression', we have discovered that over-expression of IL13Ra2 increases cancer invasion and metastasis and shortens survival time of mice with human pancreatic cancer. 12 Whether this novel function of IL-13Ra2 is extendable to other human cancers is not known.…”
mentioning
confidence: 99%
“…23 IL -13R 1 chain can form a productive complex with IL-4R chain ( also known as IL -4R ) for IL-13 signal transduction. 22,24 Based on these studies, it has been proposed that IL -13R can exist in at least three different forms. 19,25 In the first form IL -13 binds to IL -13R 2, IL-13R 1, and IL -4R chains.…”
mentioning
confidence: 99%